Quartz crystal microbalance and atomic force microscopy to characterize mimetic systems based on supported lipids bilayer - Bonet, Noel F.; Cava, Daniel G.; Vélez, Marisela (Frontiers in Molecular Biosciences, 2022)
Quartz Crystal Microbalance with dissipation (QCM-D) and Atomic Force Microscopy (AFM) are two characterization techniques that allow describing processes taking place at solid-liquid interfaces. Both are label-free techniques that when used in combination, provide kinetic, thermodynamic and structural information at the nanometer scale of events taking place at the surface of supported lipid bilayers. Here we describe the basic operation principles of both techniques, addressing a non-specialized audience, and provide some examples their interest for describing biological events taking place at supported lipid bilayers (SLBs). The aim is to illustrate current strengths and limitations of the techniques and to show their potential as biophysical characterization techniques.